Dengue Virus Entry/Fusion Inhibition By Small Bioactive Molecules: A Critical Review - Naresh, Podila; Pottabatula, Shyam S.; Jubie, Selvaraj (Mini Reviews in Medicinal Chemistry, 2022)
Many flaviviruses are remarkable human pathogens that can be transmitted by mosquitoes and ticks. Despite the availability of vaccines for viral infections such as yellow fever, Japanese encephalitis, and tick-borne encephalitis, flavivirus-like dengue is still a significant life-threatening illness worldwide. To date, there is no antiviral treatment for dengue therapy. Industry and the research community have been taking ongoing steps to improve anti-flavivirus treatment to meet this clinical need. The successful activity has been involved in the inhibition of the virus entry fusion process in the last two decades. In this study, the latest understanding of the use of small molecules used as fusion inhibitors has been comprehensively presented. We summarized the structure, the process of fusion of dengue virus E protein (DENV E), and the amino acids involved in the fusion process. Special attention has been given to small molecules that allow conformational changes to DENV E protein, viz. blocking the pocket of βOG, which is important for fusion.
Keywords: hinge